Language as a Means of Strengthening Islamic Identity in the Digital Era - Anzalman, Anzalman; Bumi, Hengki Ras; Ritonga, Ahmad Roisuddin; Mursal, Mursal; Hanafi, Abdul Halim (Lughawiyah: Journal of Arabic Education and Linguistics, 2024)
The digital era has brought significant changes to various aspects of human life, including how Muslims understand, internalize, and express their Islamic identity. Language, as a fundamental means of communication, plays a strategic role in strengthening Islamic identity amidst the challenges of globalization and digitalization. This article aims to explore how language, particularly Arabic as the language of the Qur'an, along with local languages rooted in Islamic culture, can be utilized as tools for reinforcing Islamic identity. Using a qualitative approach, this study analyzes the use of language in digital media, Islamic education, and social interactions. The findings reveal that the use of Arabic in the context of worship and education provides spiritual and cognitive reinforcement of Islamic values. Furthermore, local languages rich in Islamic wisdom can serve as effective mediums to bring religious values closer to local communities. However, the use of language also faces challenges, such as distortion of meaning on social media and limited digital literacy among the younger generation. Therefore, collaborative efforts from educators, scholars, and media practitioners are necessary to wisely utilize language as a tool for strengthening Islamic identity, enabling Muslims to address the challenges of the digital era without losing their traditional roots and Islamic values.